Integrating Coastal Culture in the Development of Problem-Solving Skills in Early Childhood - Nadia Aliyatuz Zulfa; Sigit Purnama (Universitas Al-Hikmah Indonesia, 2025)
This study aims to describe the experience of children aged 4–5 years in developing problem-solving skills through the integration of coastal culture in early childhood education. The background of this research departs from the need to strengthen contextual learning that provides space for children to explore, think critically, and work together through real experiences that are close to their lives. The research method used is qualitative with a phenomenological approach. The subjects of the study included 12 children, a teacher, and three parents. Data were obtained through participatory observation, semi-structured interviews, and documentation, then analyzed through bracketing stages, identification of important statements, grouping of themes, and preparation of textural and structural descriptions. The results of the study show that coastal culture provides a rich and meaningful context for children to recognize problems, analyze causes, and choose solution strategies. Children are able to identify problems in games such as simulating fish markets, loading and unloading boats, and pulling nets, as well as developing cognitive, social, and motor strategies. Coastal culture-based learning also improves cooperation, independence, and children's ability to try solutions independently before asking for help. This study concludes that coastal cultural integration is effective as a contextual learning model that supports early childhood problem-solving skills. The contribution of this research lies in the development of local culture-based learning alternatives that are relevant, meaningful, and can be applied in early childhood education practice.